The instrumentalization of post-truth politics in Turkey: the case of the 2023 elections - Haksever, Oguz Ufuk; Soezen, Ahmet (Routledge Journals, Taylor & Francis Ltd, 2024)
The global rise of populism has led to efforts to create an 'alternative truth' to support populist political aims. This is recently seen in Turkey in the use of post-truth political discourse by the AKP as a primary election campaign strategy. This study investigates how the AKP used post-truth politics to create an alternative truth about the opposition. The main argument of the article is that the AKP used instrumentalization of post-truth politics as a tool to reproduce biases and opinions about the opposition, which contributed to its entire strategy of winning the ballot box in the 2023 Turkish elections.
Keywords: Post-truth; populism; elections; AKP; Turkish politics